The Dynamics of the Labor Markets in Chile - Lima, Víctor (Estudios de Economía, 2016)
Through flows from 3 states, employment, unemployment and out of the laborforce, we analyze the dynamics of labor markets in Chile from 1962-2007. Weidentify some periods of different labor market regimes and relate them withchanges in flexibility. We found that reforms such as that of 1967, which introducedthe “just cause” requirement to fire workers, did not help workers to keep theirjobs, but there is no evidence of significant changes in inflexibility. Other laborregimes significantly affected transitions, but surprisingly, it was the new regimeidentified in 1990, that increased mobility. We interpret this as the result of theconsolidation of a flexibility prone model that, until then, had been associatedwith an unpopular imposition by the military regime. Finally, we do not findany evidence showing that after 1998 the changes in labor participation andconsequently, that the explanations of the changes in the unemployment ratecould be associated with “added and discouraged worker effects.”